The Translation Strategies of Metaphors in Dee’s Supernova: the Knight, the Princess, and the Falling Star - Kaparang, Alexander I.; Putranti, Adventina (Universitas Sanata Dharma, 2017)
The metaphors in Dee’s Supernova: The Knight, The Princess, and The Falling Starare translated in various ways. This paper discusses the translation of the metaphors in the work. Newmark’s Translation Strategies and Metaphor Translation Procedures are employed as the theoretical framework. The result shows that the majority of the translation of the metaphors manages to maintain their metaphorical expressions. Imitative Translation is mostly employed while the rest applies Functional Communication. Establishing the link between Translation Strategies and Metaphor Translation Procedures underlying the principle of translating metaphors is highlighted. It is also found out that the sense of each metaphor becomes the key in translating metaphors. Keywords: metaphors, translation strategies, translation procedures